Infection prevention practices and associated factors among healthcare professionals in West Gojjam Zone public Hospitals Northwest Ethiopia, 2023 - Muluken Kindu; Muluken Azage Yenesew; Genet Gedamu Kassie (PLoS ONE, 2026)
Background Inadequate adherence to infection prevention and control standards places millions of patients and healthcare workers at risk of infectious diseases worldwide, including healthcare acquired infections. Effective infection prevention and control measures and interventions have been done after the occurrence of the COVID-19 pandemic; however, there is no data that shows infection prevention and control practice of healthcare professionals in West Gojjam zone hospitals. Objective To assess infection prevention practice and associated factors among healthcare professionals in West Gojjam Zone public hospitals. Methods A mixed institutional-based cross-sectional study was conducted among healthcare professionals in West Gojjam Zone public hospitals from March 10 to April 10, 2023. A simple random sampling technique was used to select 454 participants. A structured self-administered questionnaire, key informant interview guide, and observational checklist were used to gather the information. The collected data was entered into Epi-data 4.6 and exported into SPSS version 27 for analysis. For quantitative data, bivariate and multivariate generalized estimating equation analysis was computed, considering p < 0.05 to be statistically significant at the final model. The qualitative data was transcribed, translated, coded, and analyzed thematically. Finally, the qualitative data triangulated with quantitative data. Result Four hundred thirty-four (95.6%) healthcare professionals participated in the study. The overall infection prevention practice of healthcare professionals in West Gojjam zone hospitals was 32.7% (95% CI: 28.29%−37.15%). Knowledge of participants (1.95, 95% CI: 1.19–3.19), attitude (AOR = 1.96, 95%CI: 1.24–3.12), profession of midwives (AOR = 0.467, 95%CI: 0.24–0.92), and working in Adet, Dembecha, Durbete, Feresbet, Finote Selam, and Liben hospitals, respectively, were the significant factors of infection prevention practice and training. Infrastructure, budget, supplies, and attitude were the challenges of infection prevention supplemented by the qualitative data. Conclusion The study revealed that overall infection prevention practice was poor. Participant’s knowledge, participant’s attitude, and participant’s profession were significant factors for infection prevention practice, and there was variation in infection prevention practice between hospitals. The identified modifiable factors are the area of intervention to improve infection prevention practices.